Characteristics of very large aspect angle E-region coherent echoes at 933 MHz - B. J. Jackel; D. R. Moorcroft; K. Schlegel (Annales Geophysicae, 1997)
The EISCAT UHF radar system was used to study the characteristics of E-region coherent backscatter at very large magnetic aspect angles (5–11°). Data taken using 60 μs pulses during elevation scans through horizontally uniform backscatter permitted the use of inversion techniques to determine height profiles of the scattering layer. The layer was always singly peaked, with a mean height of 104 km, and mean thickness (full width at half maximum) of 10 km, both independent of aspect angle. Aspect sensitivities were also estimated, with the Sodankylä-Tromsø link observing 5 dB/degree at aspect angles near 5°, decreasing to 3 dB/degree at 10° aspect angle. Observed coherent phase velocities from all three stations were found to be roughly consistent with LOS measurements of a common E-region phase velocity vector. The E-region phase velocity had the same orientation as the F-region ion drift velocity, but was approximately 50% smaller in magnitude. Spectra were narrow with skewness of about +1 (for negative velocities), increasing slightly with aspect angle.